Influence of the void ratio of cellular concrete on the corrosion of steel reinforcement - Gomes do Nascimento, Carlos Fernando; de Azevedo Demétrio Filho, Alexandre; Marques da Silva, Thaís; Barreto Monteiro, Eliana Cristina; Teixeira, I. A. R.; Neves, D. C. M. (Revista ALCONPAT, 2022)
The objective of this study was to understand whether voids intensify the triggering of reinforcement corrosion in cellular concrete, for slabs with light specific masses. The methodology was based on four tests: visual inspection, corrosion potential, electrical resistivity, and mass loss. In relation to the L1 family, the L2 and L3 families (higher air content) were shown to be more susceptible to reinforcement corrosion and mass loss from the steel bars in 90% of cases. However, the behavior of some slabs indicates the possibility of the process being asymptomatic with regard to staining, considering that the influence of the cover on the corrosion of the steel bars was verified.